Delphi-based strategic issue management: crafting consumer goods supply chain strategy - Förster, Bernadette; Keller, Jonas; von der Gracht, Heiko; Darkow, Inga-Lena (International Journal of Physical Distribution & Logistics Management, 2014)
Purpose ? Consumer goods supply chains (SCs) are characterized by continuously changing customer trends. Early detection of these trends is crucial for deriving successful long-term SC strategies. The purpose of this paper is to present a systematic process to support decision makers in assessing future-relevant issues and developing strategies. Design/methodology/approach ? In order to contribute to the quality of long-term decision making for SC strategy, we combine strategic issue management (SIM) and corporate foresight methodology. The authors develop a procedure that integrates the Delphi technique and SIM to empirically demonstrate how ?Delphi-based SIM? can support SC strategy development. Findings ? The paper demonstrates how to craft a strategy for consumer goods SCs supported by Delphi-based SIM. The authors are able to include and evaluate uncertain and ambivalent future developments. Pertinent strategic issues for the consumer goods SC include: consumer demographics, automated ordering, city supply, and concept stores. For the reference company, five different strategic paths were created and evaluated. Practical implications ? It is challenging for companies to be well prepared for dynamic business environments and to successfully establish a robust SC strategy. The authors develop a systematic Delphi-based SIM for detecting and evaluating signals and integrating them into SC strategy development. Originality/value ? To date, a structured approach to integrate uncertain and ambivalent issues into SC strategy development is missing. With SIM and corporate foresight, the authors provide novel methods for strategy development in the consumer goods SC.; Purpose ? Consumer goods supply chains (SCs) are characterized by continuously changing customer trends. Early detection of these trends is crucial for deriving successful long-term SC strategies. The purpose of this paper is to present a systematic process to support decision makers in assessing future-relevant issues and developing strategies. Design/methodology/approach ? In order to contribute to the quality of long-term decision making for SC strategy, we combine strategic issue management (SIM) and corporate foresight methodology. The authors develop a procedure that integrates the Delphi technique and SIM to empirically demonstrate how ?Delphi-based SIM? can support SC strategy development. Findings ? The paper demonstrates how to craft a strategy for consumer goods SCs supported by Delphi-based SIM. The authors are able to include and evaluate uncertain and ambivalent future developments. Pertinent strategic issues for the consumer goods SC include: consumer demographics, automated ordering, city supply, and concept stores. For the reference company, five different strategic paths were created and evaluated. Practical implications ? It is challenging for companies to be well prepared for dynamic business environments and to successfully establish a robust SC strategy. The authors develop a systematic Delphi-based SIM for detecting and evaluating signals and integrating them into SC strategy development. Originality/value ? To date, a structured approach to integrate uncertain and ambivalent issues into SC strategy development is missing. With SIM and corporate foresight, the authors provide novel methods for strategy development in the consumer goods SC.